Three-Dimensional Architectures in Electrochemical Capacitor Applications – Insights, Opinions, and Perspectives - Galek, Przemyslaw; Mackowiak, Adam; Bujewska, Paulina; Fic, Krzysztof (Frontiers in Energy Research, 2020)
This review focuses on describing the current state-of-the-art in the synthesis of 3D carbon architectures for the electrochemical capacitor application. The selection is based on both template and non-template strategies. Particular attention has been paid to carbon materials because of their structural interconnection, which not only creates the desired hierarchical porous channels but also ensures high conductivity and mechanical stability. A comprehensive overview of electrode materials is presented here with a detailed discussion of composite solutions, including their advantages and disadvantages. Numerous examples from the literature are presented for individual solutions. The future challenges posed for this type of material are finally summarized.